2021
DOI: 10.1002/ehf2.13281
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolysis vs. primary percutaneous coronary intervention for ST‐segment elevation myocardial infarction cardiogenic shock

Abstract: Aims There are limited contemporary data on the use of initial fibrinolysis in ST-segment elevation myocardial infarction cardiogenic shock (STEMI-CS). This study sought to compare the outcomes of STEMI-CS receiving initial fibrinolysis vs. primary percutaneous coronary intervention (PPCI). Methods Using the National (Nationwide) Inpatient Sample from 2009 to 2017, a comparative effectiveness study of adult (>18 years) STEMI-CS admissions receiving pre-hospital/in-hospital fibrinolysis were compared with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…A prior nationwide inpatient sample study in the United States using STEMI-CS identified from administrative coding reported comparable all-cause mortality (30.8% versus 30.3%) but higher hemorrhagic complications (13.5% versus 9.9%) between fibrinolysis and pPCI-treated cohorts, though it should be acknowledged that this prior study lacks hemodynamic, time to treatment, transport, and angiographic information. 9 The present data build on previous studies with the inclusion of robust patient risk and time-to-treatment variables. We acknowledge that our results were attenuated with IPW and the study sample was likely underpowered to detect a mortality difference.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A prior nationwide inpatient sample study in the United States using STEMI-CS identified from administrative coding reported comparable all-cause mortality (30.8% versus 30.3%) but higher hemorrhagic complications (13.5% versus 9.9%) between fibrinolysis and pPCI-treated cohorts, though it should be acknowledged that this prior study lacks hemodynamic, time to treatment, transport, and angiographic information. 9 The present data build on previous studies with the inclusion of robust patient risk and time-to-treatment variables. We acknowledge that our results were attenuated with IPW and the study sample was likely underpowered to detect a mortality difference.…”
Section: Discussionmentioning
confidence: 89%
“…The 0.8% intracranial hemorrhage rate in the pharmacoinvasive cohort was low and similar to the 0.4% rates reported in other population-based analyses of STEMI-associated CS receiving fibrinolysis and the 0.5% to 1.0% risk reported in randomized trials of patients without CS. 9,30 In a seminal secondary analysis of the CULPRIT-SHOCK (PCI Strategies in Patients With Acute Myocardial Infarction and Cardiogenic Shock), Freund et al 31 reported the incidence of bleeding was 21.5% using the Bleeding Academic Research Consortium definition. Moreover, independent risk factors for bleeding identified by the authors included cardiac arrest/targeted temperature management, renal replacement therapy, MCS, and incomplete reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…≥hospital day 1; (c) ‘PCI, if the admissions received PCI at any time during the hospitalization; and (d) ‘medical management’ or no CAG/PCI if they did not receive both CAG and PCI. 29 , 30 Acute non-cardiac organ failure was divided into neurological, hematologic, renal, hepatic and respiratory failures. 29 Non-cardiac multiorgan failure was defined as involvement of ≥2 organ systems other than cardiovascular system failure.…”
Section: Methodsmentioning
confidence: 99%
“…1,3 Scant data inform us about the use of fibrinolytic therapy in STEMI-CS. 1 In a contemporary analysis of the National Inpatient Sample, Vallabhajosyula et al 5 found that patients with STEMI-CS receiving fibrinolytics (n=5297) followed by angiography and either PCI (77.4%) or coronary artery bypass grafting (15.7%) had comparable in-hospital mortality to patients treated with PPCI (n=110 452) in both unmatched and propensity-matched (n=526 per arm) comparisons. However, being an analysis of a large administrative database, variables including time to reperfusion, angiographic findings, and hemodynamic data were not available and posed important study limitations.…”
mentioning
confidence: 99%